Coorte retrospectiva de crianças e adolescentes, infectados pelo HIV por transmissão vertical, no Espírito Santo : comorbidades, mortalidade e sobrevida - Silva, Sandra Fagundes Moreira da (2015)
BACKGROUND: Early diagnosis and antiretroviral therapy in infants infected with HIV through vertical transmission, reduces HIV progression and comorbidities that can lead to death. OBJECTIVE: The goal of this study was to describe the frequency of comorbidities and to verify their distribution according to demographic, epidemiological and clinical data; to evaluate risk factors for progression to death, late diagnosis and trend of mortality in a cohort of children and adolescents infected by HIV vertical transmission in a reference hospital in the state of Espírito Santo. SPECIFIC OBJECTIVES: 1. To describe the frequency of comorbidity diagnosed after the diagnosis of HIV and verify their distribution according to demographic, epidemiological and clinical data, and according to the classification of cases in a cohort of children and adolescents with AIDS. 2. To evaluate the progression of predictors of risk factors for AIDS and death and cause of death. 3. To estimate the survival rate. METHODS: Retrospective cohort study of children and adolescents infected by HIV by vertical transmission (VT), treated at the Hospital Infantil Nossa Senhora da Glória (HINSG) from January 2001 to December 2011 in Vitória - ES / Brazil. Data collection was carried out in a specific protocol standardized, and data on comorbidities, mortality and its underlying causes were obtained from medical records, death certificates and SIM database (Mortality Information System). The aids diagnosis and comorbidities were according to CDC(Centers for Disease Control and Prevention)/1994. RESULTS: From a total of 177 patients, 97 (55%) were female and 60 (34%) were less than 1 year, 67 (38%) had 1-5 years and 50 (28%) were 6 or more years old at enrollment into the service. Median age at admission was30 months (IQR 25-75%: 5-72 months). In relation to clinical and immunological classification (146, 82.5%) had a moderate / severe status at the time of entry into service and 26 (14.7%) died. The most frequent clinical signs were hepatomegaly (81.62%), splenomegaly (63.8%), lymphadenopathy (68.4%) and persistent fever (32.8%). The most frequent comorbidities were anemia (67.2%), pneumonia / sepsis / Bacterial Meningitis (64.2%), Acute Otitis Media (AMO)/ recurrent sinusitis (55.4%), recurrent severe bacterial infections (47.4%) and dermatitis (43.1%). An association was found between clinical and immunological classification in a severe form and entry into service at less than one year old with few comorbidities (p<0.001). The total time of the follow-up of the patients was 11 years, median of five years (interquartils range, IQR: 2-8 years). At the end of the study period 132(74.6%) patients were followed up, 11 (6.2%) were transferred to other services and eight (4.5%) were lost to follow-up. Regarding death as an outcome we observed a reduction of cases over time. Most patients who died were admitted to the service with classification of severe immune clinical status (77 % -20/26) had moderate / severe anemia and were on HAART for more than 3 months (17/24-71 %). The main risk factors for death were: age <1 year (p=0.005), P.jirovecii pneumonia (p=0.010), the percentage of T lymphocyte CD4 + nadir <15% (p=0.012), chronic anemia (p=0.012), severe clinical and immune status(p=0.003), recurrent severe bacterial infections (p=0.003) and tuberculosis (p=0.037). Having started HAART before 6 months of life (early diagnosis and treatment) was associated with being alive (OR 2.86, [CI 95%: 1.12 to 7.25] p=0.027). The principal diagnosis recorded for deaths were severe bacterial infections (12/21-57%). A high survival rate was observed, with 85.3 % probability of survival for more than 10 years (95%CI: 9.6-10.7). CONCLUSIONS: Most children that had late diagnosis of HIV infection also had an increased the risk of progression to aids and death because of lack of early treatment. The trend of mortality of HIV-infected children showed a steady decline in the past two years of the study, and bacterial infections persisted as major cause of death. Therefore, improvements in prenatal care and pediatric follow-up with a view to early diagnosis of vertically infected children should be part of comprehensive care for children with AIDS which could reduce mortality of these children.